Large drainage systems produced half of Mars’ ancient river sediment - Abdallah S. Zaki; Timothy A. Goudge; David Mohrig (Proceedings of the National Academy of Sciences, 2025)
Large, continental-scale drainage systems occupy nearly half of Earth’s land, shaping diverse ecosystems, with their activity primarily driven by climate and tectonism. Here, we investigate whether Mars, which lacks Earth’s tectonism, has similarly large drainage systems that could have impacted the extent of habitable environments, sediment transport, and the formation of large sedimentary basins. We reconstruct large drainage systems using globally mapped ancient martian water-formed topography—valley networks, outlet canyons, and fluvial depositional systems—revealing large drainage systems (>10 5 km 2 ) similar in scale to those on Earth. However, collectively these systems cover only ~5% of ancient martian terrain (>3.7 Ga), approximately nine times less than their counterparts on Earth. This estimate is conservative due to erosion, burial, and impact cratering, which have likely modified their preservation. Nevertheless, when quantifying the eroded sediment volumes from these large drainage systems, we show that they contributed nearly half (42%) of Mars’ ancient river-sediment budget. We further calculated the sediment eroded from large drainage systems surrounding the largest known fluvial depositional landforms on Mars and found that they potentially contributed ~21% of the planet’s river sediment budget, which we hypothesize facilitated the buildup of these sedimentary features. Our results indicate that although a substantial portion of Mars’ fluvial sediment was routed through large-scale drainage systems, sediment transport was predominantly accomplished within smaller-scale local basins. This drainage structure likely created a mosaic of habitable environments across the surface and facilitated significant sediment accumulation in a limited number of large sedimentary basins.